Enhancing Cross Cultural Communication Skills of FL Learners of Arabic through Contextual Reading of Saadallah’s Plays: Exploring Saadallah Wannous's Plays for Enhancing Cross Cultural Communication Skills of Arabic Learners (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The language and culture both are deeply rooted. A language cannot be understood completely without the knowledge of its cultural background. Similarly, a culture cannot be perceived comprehensively without its language. Therefore, language is not just about structures and words but there is a world inside any language and that world is known through its culture. This culture has always a crucial role to form its structure and impact in the particular language. This article will explain how Saadallah Wannous's plays provide a suitable ground for both - communicative competence and discourse competence. Characters, plot, and settings open the world of Arabic language and Arab culture which can foster better understanding of cross cultural skills for a foreign language learner.